THE MODERATING EFFECT OF ENVIRONEMENTAL FACTORS AND FIRM’S AGE ON STRATEGIC ORIENTATIONS AND PERFORMANCE OF INDIAN WOMEN ENTREPRENEURS - R.Jeyakodeeswari, C.Muthuveld ayutham, (International Journal of Scientific Research and Management (IJSRM), 2014)
Strategic orientation has become a central concept in the domain of entrepreneurship that has received a substantial amount of theoretical and empirical attention..Many researchers have neglected to study the role of strategic orientation in the context of women entrepreneurs. .Inspite of the cultural barriers in India, the Indian women entrepreneurs have struggled to prove themselves in specific industries though proper application of a set of strategic orientations and through demonstrating both financial and non-financial performances. The Resource Based View of the firm, when applied to women entrepreneurs, established varied results because, the environmental factors played a major role in their firms success. This study established a relationship between strategic orientations and performance under a new condition where the environmental munificence acted as a significant moderator. The study adopted Hierarchical regression analysis to test the hypothesis for the purpose. The results concluded that only under a specific environmental condition, a women entrepreneur can perform well and suggested the government to take efforts to develop such environments.